Peran Pendidikan Teologi dan Kepemimpinan Kristen dalam Pembentukan Karakter Guru Sekolah Minggu - Yunida Bawamenewi; Lidia Marbun; Andreas Fernando; Reni Triposa (SIKIP: Jurnal Pendidikan Agama Kristen, 2022)
Theological education actually has an important role for Sunday school teachers in giving a more specific understanding to a teacher in guiding, directing, and educating Sunday school children. Because Sunday school is a place for character building, attitude, and introduction of children from an early age about the truth of God's word. Not only theological education has an important role for Sunday school teachers, Christian leadership also has an important role for Sunday school teachers. Christian leadership is leadership that has the heart of a servant in serving others where the model is Jesus. A Christian leader has a very strong influence on Sunday school teachers in bringing positive changes to Sunday school teachers so that the teacher is able to transform this positive influence on Sunday school children. This writing uses a literature research method where this research method is carried out with a descriptive qualitative approach so that it can describe the role of theological education and Christian leadership for Sunday school teachers because theological education and Christian leadership are the basis for Sunday school teachers in teaching children. Sunday school kids.  AbstrakPendidikan teologi sesungguhnya memiliki peran penting untuk guru sekolah Minggu dalam memberi pemahaman ynag lebih spesifik kepada seorang guru dalam membimbing, mengarahkan dan mendidik anak sekolah Minggu. Oleh karena sekolah Minggu merupakan wadah pembentukan karakter, sikap dan pengenalan anak sejak dini tentang kebenaran firman Tuhan. Tidak hanya pendidikan teologi saja yang memiliki peran penting bagi guru sekolah Minggu, kepemimpinan kristen juga memiliki peran penting bagi guru sekolah Minggu. Kepemimpinan kristen adalah kepemimpinan yang memiliki hati seorang hamba dalam melayani orang lain dimana yang menjadi modelnya adalah Yesus. Seorang pemimpin kristen memiliki pengaruh yang sangat kuat bagi guru sekolah Minggu dalam mebawa perubahan positif bagi guru sekolah Minggu sehingga guru tersebut mampu mentransformasi pengaruh positif tersebut kepada anak sekolah Minggu. Penulisan ini menggunakann metode penelitian pustaka dimana metode penelitian ini dilakukan dengan pendekatan kualitatif deskriptif, sehingga dapat mengdeskripsikan peran pendidikan teologi dan kepemimpinan kristen itu bagi guru sekolah Minggu, oleh karena pendidikan teologi dan kepemimpinan kristen ini merupakan dasar bagi para guru sekolah Minggu dalam mengajar anak-anak sekolah Minggu.